Analisis Kualitatif Transformasi Strategi Pemasaran UMKM Melalui Pemanfaatan Generative AI Video pada Produk Parfum - Kuntoro, Cahyo Dwi; Kifayah, Muhammad Naufal; Fadilah, Ridha Tasya (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research aims to analyze the transformation of marketing strategies in perfume MSMEs through the utilization of Generative AI Video technology. Amidst intense competition in the creative industry, MSMEs face significant challenges related to the high cost of professional visual content production. Using a descriptive qualitative approach, this study explores how tools shift from manual video production to the use of text-to-video based artificial intelligence. Data were collected through in-depth interviews with perfume MSME owners who have adopted AI technology in their promotional activities. The results indicate that the utilization of Generative AI Video significantly transforms marketing strategies in three main aspects: production cost efficiency, content distribution speed, and the ability to visualize scents more imaginatively. This technology allows MSMEs to create aesthetic visual narratives without physical resource constraints, thereby enhancing brand competitiveness on digital platforms. This study concludes that AI adaptation is not merely an efficiency tool, but a catalyst for creativity that changes how MSMEs build brand identity visually.